PENGARUH DESAIN PRODUK, PERSEPSI HARGA DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO DI KOTA SUMBAWA - Astari, Navila Riski; Sugiarto, Aris (Jurnal Nusa Manajemen, 2025)
This study aims to test the influence of Product Design, Price Perception and Content Marketing on Oppo Smartphone Purchasing Decisions in Sumbawa City. This study uses a quantitative method with an associative approach. Determination of the sample using purposive sampling technique totaling 160 respondents who are people in Sumbawa City based on the Hair formula. Primary data processing using the Statistical Package for Social Science (SPSS) with the data analysis technique used is multiple linear regression. The results of this study obtained: Product Design has a significant positive effect on Oppo smartphone purchasing decisions in Sumbawa City. Price Perception has a significant positive effect on Oppo smartphone purchasing decisions in Sumbawa City. Content Marketing has a significant positive effect on Oppo smartphone purchasing decisions in Sumbawa City.